Ecosystem service multifunctionality of low‐productivity forests and implications for conservation and management. Issue 4 (16th February 2020) - Jönsson, Mari; Snäll, Tord
Abstract: Low‐productivity forests are often the last remaining pristine forests in managed forest landscapes and typically overrepresented among protected forests. However, the provisioning of individual and multiple ecosystem services (ES‐multifunctionality) by these forests remains poorly assessed, making it difficult to evaluate their importance in forest conservation and management. Here, using nationwide data on ES from over 2, 000 forest plots, we test whether levels of ES‐multifunctionality and individual ES differ between low‐productivity forested mires and rocky outcrops in relation to the levels of productive forests, and as a function of forest age, tree species richness and climate. We defined ES‐multifunctionality using different threshold values of the maximum levels (low, medium and high) and weighted these according to land‐use objectives (equal weight of all services, greater weight to cultural and supporting ES or greater weight to production). We show that the ES‐multifunctionality of forested mires is consistently lower than those of productive forests. However, the ES‐multifunctionality increased with forest age in forested mires but not in productive forests. The ES‐multifunctionality of forested rocky outcrops, on the other hand, was higher or equivalent to that of productive forests under equal weight and supporting land‐use objectives, respectively. Our findings highlight that forested rocky outcrops can supply multiple ES, especially older forested stands with mixtures of coniferous and deciduous trees. Generally, we found no evidence for strong trade‐offs between the ES studied and our results highlight the importance of forest age for increasing the ES‐multifunctionality of low‐productivity forests. Synthesis and applications . Low‐productivity forests should not be exempt of forestry or protected purely based on low productivity or low land‐use conflict if the goal is to conserve multiple ecosystem services (ES). Inclusion grounds for protecting low‐productivity forests should instead carefully consider the site type (dry vs. wet), forest age and tree species richness. To maintain higher ES‐multifunctionality in low‐productivity forests, older or deciduous trees should also not be harvested. This will require changes in current conservation or management policies of low‐productivity forests of some countries. Abstract : Low‐productivity forests should not be exempt of forestry or protected purely based on low productivity or low land‐use conflict if the goal is to conserve multiple ecosystem services (ES). Inclusion grounds for protecting low‐productivity forests should instead carefully consider the site type (dry vs. wet), forest age and tree species richness. To maintain higher ES‐multifunctionality in low‐productivity forests, older or deciduous trees should also not be harvested. This will require changes in current conservation or management policies of low‐productivity forests of some countries. Svensk sammanfattning: Skogar med låg produktivitet (impediment) är ofta de sista återstående orörda skogarna i det brukade skogslandskapet och överrepresenterade bland skyddade skogar. Vilka enskilda ekosystemtjänster (ET) och sammanvägda ekosystemtjänster (ET‐multifunktionalitet) som tillhandahålls av dessa skogar är dåligt undersökt, vilket gör det svårt att utvärdera deras betydelse för skoglig naturvård. Här använder vi rikstäckande data om ET från över 2000 skogliga provytor för att testa om nivåerna av ET‐multifunktionalitet och enskilda ET skiljer sig mellan lågproduktiva skogliga myrimpediment och bergimpediment i förhållande till produktiva skogar, och som en funktion av skogens ålder, antalet trädarter och klimat. Vi definierade ET‐multifunktionalitet med hjälp av olika tröskelvärden för maximala nivåer (låga, medelhöga och höga) och viktade dessa enligt tre olika scenarier för markanvändning (lika vikt för alla tjänster, större vikt till kulturella och stödjande tjänster, eller större vikt för försörjande produktionsinriktade tjänster). Resultaten visar att ET‐multifunktionaliteten hos skogliga myrimpediment var konsekvent lägre än för produktiva skogar. ET‐multifunktionaliteten ökade emellertid med skogens ålder hos myrimpediment, men inte på motsvarande sätt i de produktiva skogarna. ET‐multifunktionaliteten för de skogliga bergimpedimenten var högre eller motsvarande den för produktiva skogar när alla ET viktades lika eller när stödjande och kulturella tjänster viktades upp. Våra resultat visar att skogliga bergimpediment kan förse flera ET, särskilt äldre bergimpediment med en blandning av barr‐ och lövträd. Generellt sett hittade vi inga bevis för starka avvägningar (konflikter eller synergier) mellan de studerade ET och våra resultat belyser vikten av skogens ålder för att öka ET‐multifunktionaliteten i lågproduktiva skogar. Syntes och tillämpningar . Skogar med låg produktivitet (impediment) bör inte undantas från skogsbruk eller skyddas enbart baserat på låg produktivitet eller låg markanvändningskonflikt om målet är att bevara flera ekosystemtjänster (ET). En grund för att skydda lågproduktiva skogar bör istället noga överväga markförhållanden (berg kontra myr), skogens ålder och antalet trädslag. För att upprätthålla högre ET‐multifunktionalitet i skogar med låg produktivitet bör äldre träd och lövträd inte avverkas. Detta kräver förändringar i nuvarande skötsel och policy för skogliga impediment i vissa länder.